Comments on Properties of Gas Rich Dwarfs Galaxies in the Range of Radio Frequencies (B-Band) - Al-Mashhadani, Layali Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this project we analyze data of a large sample of gas rich dwarfs galaxies including; Low Surface Brightness Galaxies (LSBGs), Blue Compact Galaxies (BCGs), and dwarfs Irregulars (dIr). We then study the difference between properties of these galaxies in the range of radio frequencies (B-band). The data are available in HIPASS catalogue and McGaugh’s Data Page. We depended also NASA/IPACExtragalactic Databes web site http://ned.ipac.caltech.edu in the data reduction. We measured the gas evolution (HI mass), gas mass-to-luminosity ratio, and abundance of the elements such as the oxygen abundance for these galaxies. Our results show a big discrepancy between the behavior of LSBGs at low and high luminosity ranges. We find that the LSBGs have higher HI masses than other samples of BCGs. BCGs are forced to stem from LSBGs or from dlrs according to their gas to light ratio vs total luminosity value